2006
DOI: 10.1258/095646206778691185
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of syphilis assays in detecting different stages of early syphilis

Abstract: Our aim was to determine the sensitivity of the Murex ICE enzyme immunoassay (EIA) as a screening test for early syphilis and to determine how many additional cases of infection were detected by performing additional tests when requested on clinical grounds. This was an observational study on consecutive patients diagnosed with syphilis in the Department of Genitourinary Medicine, Edinburgh between January 1st 2004 and April 1st 2005. Additional tests were performed on sera that gave a positive or equivocal EI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 0 publications
3
29
3
1
Order By: Relevance
“…It is highly desirable that a suitable confirmatory test should have, at least, sensitivity and specificity equivalent to those of the screening assay. Manavi and colleagues (16) have suggested that, in the absence of a specific treponemal IgM EIA, a TPPA test should be performed whenever there (Table 3). Traditionally, the FTA-ABS test is regarded as the "gold standard" for confirmatory syphilis serology (2,20).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly desirable that a suitable confirmatory test should have, at least, sensitivity and specificity equivalent to those of the screening assay. Manavi and colleagues (16) have suggested that, in the absence of a specific treponemal IgM EIA, a TPPA test should be performed whenever there (Table 3). Traditionally, the FTA-ABS test is regarded as the "gold standard" for confirmatory syphilis serology (2,20).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 17 (34%) cases of primary syphilis were initially negative by EIA, which had a sensitivity of 57% when compared with dark ground microscopy 4. Another recent evaluation reported a sensitivity of 84% for the Murex immune capture enzyme (ICE) immunoassay in detecting primary syphilis 5. Commercially available EIAs vary in their ability to detect primary syphilis,6 7 Although dark ground microscopy has high sensitivity in the diagnosis of primary syphilis, it is not widely used and is only performed in 29% of cases nationally 3…”
mentioning
confidence: 99%
“…In recent years, ELISAs and CLIAs have been developed and evaluated as treponemal diagnostic tests for syphilis, including the Murex Syphilis ICE test, the Architect Syphilis test, and others [7][8][9][10][11]; several of these assays are based on specific T. pallidum recombinant antigens. However, several limitations exist regarding the widespread use of these automated methods, such as the requirement for specialized techniques and equipment that are not commonly available in developing countries.…”
Section: Discussionmentioning
confidence: 99%